Excellent cyclic performance of Fe2O3@C/SnO2 controlled by Fe2O3@C and SnO2/C hybrid structures for lithium-ion batteries. (September 2019) - Wang, X.M.; Wang, N.; Zhang, Q.; Shi, X.F.; Yu, Y.N.; Chai, Y.J.
Abstract: A ternary nanocomposite Fe2 O3 @C/SnO2 is synthesized via a two-step hydrothermal method with further annealing. The crystallinity, micromorphology, and electrochemical performance of Fe2 O3 @C/SnO2 nanocomposite are systematically characterized. Galvanostatic charge/discharge measurement demonstrates that Fe2 O3 @C/SnO2 exhibits good rate discharge capacity. It shows a reversible capacity of 540 mAh g −1 after 1000 cycles operated at a current density of 1000 mA g −1, with higher Coulombic efficiency. The excellent electrochemical properties of Fe2 O3 @C/SnO2 maybe are related to the hybrid structure, in which the carbon layer encloses the needle Fe2 O3, meanwhile, the SnO2 nanoparticles disperse into carbon layer. The carbon layer effectively refines the pulverization of SnO2 nanoparticles and avoids the aggregation. The carbon layer loaded SnO2 encircles Fe2 O3, which effectively accommodates the internal stress of volume expansion of Fe2 O3 . The results demonstrate that such the nanocomposite developed here has great potential for application in high-energy lithium-ion batteries. Highlights: Fe2 O3 @C/SnO2 composite is composed of Fe2 O3 @C and C/SnO2 hybrid structures. The discharge specific capacity shows a sustained increase after 150 cycles, even after 1000 cycles. The discharge capacity reaches 540 mAh g −1 after 1000 cycles at 1000 mA g −1 .